Overview of Knowledge, Attitudes, and Behaviors Related to Halitosis in Online Motorcycle Taxi Drivers in Sei Putih Tengah Sub District, Petisah District, Medan, Indonesia - Suci Erawati; Idamawati Nababan; Anisa Ulfah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Halitosis is a sign of dental and oral health problems. Halitosis is characterized by the presence of an unpleasant odor in the oral cavity. Halitosis is caused by many things, one of which is a result of impaired saliva production, which is caused by smoking. Online motorcycle taxi drivers are in a community that is very close to smoking. This study aimed to provide an overview of aspects of knowledge, attitudes, and behavior related to halitosis in online motorcycle taxi drivers in Sei Putih Tengah Sub District, Petisah District, Medan, Indonesia. Methods: Descriptive observational study. A total of 36 research subjects, namely online motorcycle taxi drivers, participated in this study. Observation of knowledge, attitudes, and behavior refers to a questionnaire developed by the halitosis clinic at the University of Basel, Switzerland. Univariate analysis was carried out with the help of SPSS software. Results: The majority of research subjects are independently aware of bad breath and experience similar complaints <1 year. The majority of research subjects felt bad breath after waking up in the morning. The majority of research subjects also stated that dentists were the choice for consultation regarding bad breath disorders. The majority of research subjects know the origin of bad breath, the source of bad breath, and know that smoking is the cause of bad breath. Most research subjects did not feel ashamed of other people even though they felt they had bad breath. Conclusion: Knowledge and behavior related to halitosis are good, although attitudes related to halitosis are not good among online motorcycle taxi drivers in Sei Putih Tengah Sub District, Petisah District, Medan, Indonesia.